The Role of E-CRM and E-Marketing Increasing Market Orientation In Alligator Roastery Medan - Pesta Gultom; shendy; Elisabeth Nainggolan (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
This study aims to determine the influence of E-CRM and E-Marketing on Market Orientation in Alligator Roastery. This research uses descriptive and quantitative methods as well as data sources in the form of primary and secondary data. The population in the study is all consumers on Alligator Roastery by 2023. The sample size is 110 consumers with a tolerable error rate of 5%. The data were analyzed by multiple linear regression analysis method. The results showed that E-CRM partially had no positive and insignificant effect on Market Orientation at Alligator Roastery. E-Marketing partially has a positive and significant effect on Market Orientation in the Café Alligator Roastery business. Based on the results of hypothesis testing simultaneously, it is known that the results of the F-test show that E-CRM and E-Marketing simultaneously affect Market Orientation in Alligator Roastery. The magnitude of R Square is 50.3% which means that E-CRM and E-Marketing can explain their influence on Market Orientation by 50.3%.